Precise tuning of gene expression levels in mammalian cells - Michaels, Y; Barnkob, M; Barbosa, H; Baeumler, T; Thompson, M; Andre, V; Colin-York, H; Fritzsche, M; Gileadi, U; Sheppard, H; Knapp, D; Milne, T; et al. (Springer Nature, 2019)
Precise, analogue regulation of gene expression is critical for cellular function in mammals. In contrast, widely employed experimental and therapeutic approaches such as knock-in/out strategies are more suitable for binary control of gene activity. Here we report on a method for precise control of gene expression levels in mammalian cells using engineered microRNA response elements (MREs). First, we measure the efficacy of thousands of synthetic MRE variants under the control of an endogenous microRNA by high-throughput sequencing. Guided by this data, we establish a library of microRNA silencing-mediated fine-tuners (miSFITs) of varying strength that can be employed to precisely control the expression of user-specified genes. We apply this technology to tune the T-cell co-inhibitory receptor PD-1 and to explore how antigen expression influences T-cell activation and tumour growth. Finally, we employ CRISPR/Cas9 mediated homology directed repair to introduce miSFITs into the BRCA1 3'UTR, demonstrating that this versatile tool can be used to tune endogenous genes.